2014
DOI: 10.1002/jssc.201301173
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of ribavirin in human plasma and red blood cells using LC-MS/MS

Abstract: LC-MS/MS has been applied for the rapid determination of the nucleoside analogue ribavirin in human plasma and red blood cells. The incorporation of ribavirin to the erythrocytes has been assayed after in vitro incubation of the cells at different concentrations of the antiviral drug. After protein precipitation, samples were injected into a C8 column, achieving a complete separation of ribavirin from the endogenous isobaric compound uridine. Calibration ranges varied from 10 to 10,000 ng/mL in plasma and from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…As for LC-UV methods, also with LC-MS methods the chromatographic separation of antiviral compounds is typically carried out on C18 columns, but some methods based on the use of C8 columns [ 147 , 148 ], as well as one based on the use of a C30 column were also proposed [ 39 ]. As mobile phases, MeOH, ACN and ultrapure water added with formic acid have been mainly employed.…”
Section: Sample Pre-treatment and Extraction Of Covid-19 Antiviral Drmentioning
confidence: 99%
“…As for LC-UV methods, also with LC-MS methods the chromatographic separation of antiviral compounds is typically carried out on C18 columns, but some methods based on the use of C8 columns [ 147 , 148 ], as well as one based on the use of a C30 column were also proposed [ 39 ]. As mobile phases, MeOH, ACN and ultrapure water added with formic acid have been mainly employed.…”
Section: Sample Pre-treatment and Extraction Of Covid-19 Antiviral Drmentioning
confidence: 99%
“…From the literature review, it was observed that there are some methods used for the estimation of Ribavirin in biological matrices, such as serum (Danso et al, 2011), human plasma (Ferreiros et al, 2014;Loregian et al, 2007), rat plasma, and brain (Shi et al, 2015;Zironi et al, 2011), but no analytical method has been developed for the estimation of Ribavirin in its formulation. Furthermore, the reported methods on biological matrices were less sensitive to the quantification limit of more than 5 ng/ml and the run time of more than 5 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…LC–MS/MS is widely utilized and often guarantees high levels of both selectivity and sensitivity when analyzing compounds at low concentrations in biological samples. Several LC–MS/MS methods have been established for the determination of drugs and toxic compounds in rat brain , human blood (including whole blood, plasma, serum) and urine , and gastric content . However, in these studies, barbital, phenobarbital, and secobarbital were not always included, which are still quite often used in China.…”
Section: Introductionmentioning
confidence: 99%